Difference in body image, Pocket Money and Food Intake with Nutritional Status in High School Adolescents - Fahneta, Hairunnisa; Mahpolah; Rahmani (Jurnal Riset Pangan dan Gizi, 2026)
Adolescents require more nutrients due to their growth and development. According to the 2018 Riskesdas data, adolescents aged 16-18 in Banjar Regency have a prevalence of malnutrition of 15,3%, which is higher than that of South Kalimantan at 12,3%. This study aims to determine the differences in body image, pocket money, and food intake with the nutritional status of adolescents at SMAN 1 Martapura and SMAN 3 Martapura and to determine the differences in variables between schools. This is an analytical observational study with a cross-sectional design. The population consisted of all 10th and 11th grade adolescents at SMAN 1 Martapura (350 adolescents) and SMAN 3 Martapura (91 adolescents). A sample of 55 and 37 adolescents was taken using proportional random sampling. Primary data were obtained through questionnaires, interviews, and measurements of weight and height. Bivariate analysis was performed using the Kruskal-Wallis and Mann-Whitney tests. The results showed that there were no significant differences in body image (p=0,528), pocket money (p=0,566), energy intake (p=0,831), and protein intake (p=0,503) with the nutritional status of adolescents at SMAN 1 Martapura. while at SMAN 3 Martapura, there were no significant differences in body image (p=0,262), energy intake (p=0,345), and protein intake (p=0,356). However, there were significant differences in pocket money (p=0,041) and nutritional status. The results of the comparison test between schools showed a significant difference in body image (p=0,014) and pocket money (p=0,000) and no significant difference in energy intake (p=0,366) and protein intake (p=0,268).